Membangun Ketahanan Terhadap Bencana: Strategi Kebijakan Global dalam Menangani Pengungsi Iklim - Ria Silviana; Hieronymus Soerjatisnanta (Fakultas Hukum, Universitas Warmadewa, 2025)
Climate change has emerged as a critical global issue, resulting in significant impacts such as rising temperatures, polar ice melt, and escalating sea levels, which threaten millions of lives. According to the Intergovernmental Panel on Climate Change (IPCC), approximately 3.3 to 3.6 billion people reside in areas highly vulnerable to climate change. This has led to an increasing number of climate-induced displacements, with millions of individuals—referred to as